The Shoreline Retreat and Spatial Analysis over the Coastal Water of Belawan - A. Perwira Mulia Tarigan; Wiwin Nurzanah (Universitas Lampung, 2016)
Abstract – An examination of shoreline retreat is conducted over the muddy coast in the vicinities of the port of Belawan. The related sea level rise is estimated using the well-known Bruun Rule based on the characteristics of mud profile prevalent along the eastern coast of North Sumatera Province. The spatial analysis involved is done utilizing the concept and procedure of GIS. The averaged shoreline retreat over the hot spot area of erosion, i.e. 18 m per year, implies that the relative rate of sea level rise is in the range of 14 to 18 mm per year, indicating an extremely severe rate. In addition, three other cases of simple GIS applications related to coastal water of the port are spatially demonstrated. Keywords – coastal water, coastal erosion, sea level rise, and GIS